Peculiarities of ecosystem monitoring on the territory of Donskoy natural park - N. O. Ryabinina (Юг России: экология, развитие, 2015)
The article deals with peculiarities of ecosystem monitoring as an important part of scientific and research work on Donskoy natural park of Volgograd region.One of the most significant tasks of functioning of national and natural parks, besides preservation and restoration of zonal and other geosystems, is scientific and research work. It is crucial for planning and administration of activity of natural parks, particularly for estimation and prognosis of the ecological situation within and beyond the park territory.